2018
DOI: 10.3389/fpls.2018.01038
|View full text |Cite
|
Sign up to set email alerts
|

Plant Small Non-coding RNAs and Their Roles in Biotic Stresses

Abstract: Non-coding RNAs (ncRNAs) have emerged as critical components of gene regulatory networks across a plethora of plant species. In particular, the 20–30 nucleotide small ncRNAs (sRNAs) play important roles in mediating both developmental processes and responses to biotic stresses. Based on variation in their biogenesis pathways, a number of different sRNA classes have been identified, and their specific functions have begun to be characterized. Here, we review the current knowledge of the biogenesis of the primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(54 citation statements)
references
References 124 publications
(144 reference statements)
0
51
0
Order By: Relevance
“…As important epigenetic elements, non-coding RNAs (ncRNAs) widely regulate plant multiple processes, including growth, development and even responses to environmental stresses. Based on the size, ncRNA can be divided into short-chain non-coding RNAs and long-chain non-coding RNA [93][94][95]. In the past few decades, enormous studies in animals and plants have revealed that short-chain non-coding RNAs, such as microRNAs (miRNA) and small interfering RNAs (siRNAs), participate in both transcriptional and post-transcriptional regulation of gene expression [93][94][95].…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…As important epigenetic elements, non-coding RNAs (ncRNAs) widely regulate plant multiple processes, including growth, development and even responses to environmental stresses. Based on the size, ncRNA can be divided into short-chain non-coding RNAs and long-chain non-coding RNA [93][94][95]. In the past few decades, enormous studies in animals and plants have revealed that short-chain non-coding RNAs, such as microRNAs (miRNA) and small interfering RNAs (siRNAs), participate in both transcriptional and post-transcriptional regulation of gene expression [93][94][95].…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…Both siRNAs and miRNAs are processed from dsRNA precursors by the ribonuclease Dicer, and both can regulate gene expression. RNAi participates in the regulation of diverse biological processes including plant immunity (Brant and Budak, 2018;Deng et al, 2018), and several siRNAs and miRNAs have been described as important players in plant defense against viruses, bacteria, and fungi (Hua et al, 2018;Rosa et al, 2018;Muhammad et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Since small RNAs are sequence-dependent negative regulators of gene expression involved in many relevant plant processes such as development, genome stability, or stress response (biotic and abiotic) [1,19,20], the proposed cloning strategy represents an straightforward tool to characterize many aspects related with small RNA biology, and as such could potentially become a valuable asset for the research community.…”
Section: Introductionmentioning
confidence: 99%